Pengaruh Visibility, Credibility, Attraction dan Power Celebrity Endorse terhadap Brand Image (Studi pada Mahasiswa FEB UNISMA Angkatan 2016-2018 pengguna Shopee) - Muhammad Fauzi; Ronny Malavia Mardani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The goal of the study is to determine the effect of visibility, credibility, attraction, and power celebrity endorse on brand image on the Shopee, buying and selling site. The population in this study was the 2016-2018 FEB Students of the University of Islam Malang who used the Shopee, buying and selling site. The number of sample is 96 respondents who were selected using a purposive sampling technique. Hypothesis testing in this study used multiple linear regression analysis. The results showed that the variables of visibility, credibility, attraction, and power celebrity endorse partially affect brand image. The variables which influenc brand image are visibility, credibility, attraction, and power celebrity. Keywords: Visibility, Credibility, Attraction, Power and Brand Image